Intention to Scan QRIS Memediasi Trust dan Attitude terhadap Use Mobile Banking - Saputri, Nemshy Elfa; Susilowati, Endah (Gorontalo Accounting Journal, 2025)
This study aims to examine how the intention to scan QRIS serves as a mediator between trust and attitude toward the use of mobile banking. A quantitative research approach was employed through the distribution of questionnaires. The population in this study consisted of students enrolled in the "Kartu Indonesia Pintar Kuliah" program at the National Development University “Veteran” East Java. A sample of 93 students was selected using probability sampling techniques. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The findings indicate that trust and attitude significantly influence the use of mobile banking; trust and attitude also influence the intention to scan QRIS; the intention to scan QRIS positively affects the use of mobile banking; and the intention to scan QRIS mediates the effect of trust on the use of mobile banking but does not mediate the effect of attitude on the use of mobile banking. The novelty of this research lies in examining the mediating role of the intention to scan QRIS, which has not been previously investigated in earlier studies.